First report of Eustrongylides sp. larvae (Nematoda: Dioctophymatidae) in Hoplias malabaricus (Characiformes: Erythrinidae) in Rondônia State, Western Amazon, Brazil - Meneguetti, Dionatas Ulises de Oliveira (2020)
This paper describes the first report of Eustrongylides sp. larvae in Hoplias malabaricus Bloch, 1794 (Characiformes: Erythrinidae) in Rondônia State, Western Amazon, Brazil, and it is more a parasite which can infect humans in that area.